Politicizing immigration in Western Europe - Edgar Grande; Tobias Schwarzbözl; Matthias Fatke (Journal of European Public Policy, 2019)
Immigration has become a hot topic in West European politics. The factors responsible for the intensification of political conflict on this issue are a matter of considerable controversy. This holds in particular for the role of socio-economic factors and of radical right populist parties. This article explores the politicization of immigration issues and its driving forces in the electoral arena. It is based on a comparative study using both media and manifesto data covering six West European countries (Austria, France, Germany, Netherlands, Switzerland, and the UK) for a period from the early 1990s until 2017. We find no association between socio-economic factors and levels of politicization. Political conflict over immigration follows a political logic and must be attributed to parties and party competition rather than to `objective pressures.' More specifically, we provide evidence that the issue entrepreneurship of radical right populist parties plays a crucial role in explaining variation in the politicization of immigration.
Keywords: 330; Europe; immigration; politicization; party manifestos; political parties